Comparative Analysis of Trending Web Development Frameworks : Angular, React and Vue.js - Hassan, Amad Ul (2024)
In the rapidly evolving landscape of web development, the choice of a framework plays a pivotal role in shaping the success of a project. This study conducts a comprehensive comparative analysis of three of the most prominent front-end frameworks: Angular, React, and Vue.js. Through an in-depth examination of their architecture, performance, ecosystem, and community support, we aim to provide valuable insights for developers, businesses, and technology enthusiasts. The study employs a systematic approach, evaluating each framework based on key parameters such as ease of learning, scalability, flexibility, and developer experience. Real-world use cases and industry trends are scrutinized to highlight the practical implications of choosing one framework over another. Additionally, the research delves into the latest updates and features introduced by Angular, React, and Vue.js, shedding light on their adaptability to emerging web development challenges. The analysis extends beyond technical aspects, exploring the broader developer community's sentiments and preferences. By examining online discussions, forums, and community engagement, the study captures the pulse of the developer ecosystem surrounding each framework. Furthermore, it investigates the impact of these frameworks on job markets and career opportunities. Through this comparative analysis, our goal is to empower developers, businesses, and decision-makers with a nuanced understanding of Angular, React, and Vue.js. Whether embarking on a new project or considering a migration, the findings of this study offer valuable guidance for making informed decisions in the dynamic realm of web development.